An unusual cause of chronic otitis media with effusion. Issue 2 (February 2014) - Cooper, L; Ford, K; Talwar, R; Wareing, M
Abstract Objective: To describe an unusual cause for hearing loss in an adult. Case report: A 37-year-old man presented with a year's history of right-sided hearing loss. He had no history of trauma, or local or systemic infection. He was otherwise well, took no medication and had no allergies. He had a two-year history of low back pain. On examination, he had a retracted right tympanic membrane with no perforation, and a middle-ear effusion. Nasendoscopy was normal. Examination of other systems was unremarkable. Computed tomography of the temporal bones with contrast demonstrated a large, right, intra-cerebral internal carotid artery aneurysm compressing the eustachian tube. After a balloon occlusion test, he underwent endovascular occlusion of the parent vessel. He made a good post-operative recovery. A subsequent abdominal ultrasound excluded an abdominal aneurysm as a cause of his low back pain. His hearing had not improved three days post-operatively, and was to be formally assessed and monitored in the clinic. Discussion: A carotid aneurysm is a rare cause of eustachian tube compression but must be considered in the differential diagnosis of conductive hearing loss. Aneurysms may have systemic causes, and their presence in other systems should be excluded as they may be multiple.